Agricultural growth and poverty in Mozambique: Technical analysis in support of the Comprehensive Africa Agriculture Development Program (CAADP) - Pauw, Karl; Thurlow, James; Uaiene, Rafael; Mazunda, John (International Food Policy Research Institute, 2013)
In this study we calibrate a CGE model to Mozambique’s newest social accounting matrix (SAM) to consider economywide growth, poverty, and nutrition impacts under alternative agricultural growth scenarios. Scenarios are compared over the period 2009–2019, which coincides with the implementation period of the Strategic Plan for Agricultural Development (PEDSA), Mozambique’s embodiment of the Comprehensive Africa Agriculture Development Program (CAADP). The “baseline scenario” assumes a continuation of Mozambique’s recent experience of low agricultural productivity and slow progress in the fight against poverty. Although national accounts estimates suggest that agricultural GDP expanded at around 7.4 percent per annum during 2003–2007, this figure has been widely questioned. In our baseline scenario, which carefully replicates historic crop production trends from official statistics, agricultural GDP only expands at 3.2 percent per annum during 2009–2019, while the economy as a whole expands at 5.7 percent per annum. The poverty headcount rate declines from 54.6 in 2008/09 (the official estimate) to 46.8 percent by 2019. The biggest decline in poverty occurs in the southern region where, following recent trends, agricultur-al productivity increases more rapidly off a very low base compared to other regions. The share of caloric deficient people declines from 57.1 percent in the base to 50.1 percent by 2019.